Do institutions, religion and the economic cycle impact bank stability in dual banking systems? - Bektas, Eralp; Elbadri, Marei; Molyneux, Philip (Wiley, 2022)
We investigate the relationship of institutional quality, religion, and economic cycles to bank stability using a sample of 254 banks, including Islamic (IBs) and conventional banks (CBs), located in nine countries (QISMUT+3) that follow dual banking systems. We use a comprehensive model and adopt a stronger econometric methodology compared with previous literature. Our findings reaffirm the significant positive influence of institutional quality on bank stability as proxied by a bank's Z-score. Institutional quality variables including financial freedom, voice and accountability, the rule of law, and political stability positively influence bank stability. On the other hand, other institutional quality variables such as economic freedom, government effectiveness, RQ, and corruption negatively affect bank stability. Overall, our empirical evidence shows that IBs are relatively less stable than CBs, due to banking practices, riskier products, and immature legal frameworks. Our analysis also suggests that IBs operate in a similar manner as CBs. New to this study, results suggest that religious orientation has no significant effect on bank stability in our sample countries with dual banking systems. Importantly, we find that the legal system, in particular the Sharia-based legal system, has no significant effect on stability for IBs. Furthermore, customer religiosity measured as the share of Muslim population does not appear to have a differential impact on stability for IBs compared to CBs except when the Muslim share in population exceeds 85%.
Keywords: bank stability; banking; institutional quality; religiosity; macroeconomics